"An informed risk assessment": a qualitative exploration of elite climbers' experiences during pregnancy and the postpartum period - Davenport, M. H.; Ray, L.; Black, J.; McHugh, T.-L. (Sports Medicine, 2025)
Background: Physical activity guidelines for pregnancy discourage activities such as climbing that have an increased risk of falling. However, as the sport of climbing has grown so has the number of athletes continuing to climb during pregnancy. Objective: The purpose of this qualitative description was to describe the experiences of elite climbers navigating pregnancy and the postpartum period. Methods: A total of 11 elite climbers who had trained and or competed at the elite level while pregnant within the last 5 years were interviewed. Data were generated via online, one-on-one semi-structured interviews with a researcher based out of Canada (June-September 2024) that were audio-recorded, transcribed verbatim, and analyzed through a process of content analysis. Results: Experiences of elite climbers during pregnancy and the postpartum period are represented by five themes: (1) decision-making around climbing risks during pregnancy, (2) modifications to mitigate risk, (3) lasting effects of climbing on pregnancy and motherhood, (4) climbing feels way better than walking: benefits of climbing during pregnancy, and (5) climbing-specific barriers to inclusion. Overall, the climbers highlighted that continued engagement in their sport was based on an informed risk assessment where they viewed the risk to themselves and their fetus to be low and the potential benefits to be very high. Conclusions: Although global guidelines recommend avoiding activities with an increased risk of trauma to the abdomen, the athletes interviewed in this study detailed their informed decision-making that balanced the potential risks associated with climbing with the potential benefits of continued participation. Future research investigating the objective risks and benefits of climbing during pregnancy is needed.